2005
DOI: 10.2460/ajvr.2005.66.1430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arterial pressure waveform analysis with the lithium dilution technique to monitor cardiac output in anesthetized dogs

Abstract: The PCO system tracked changes in CO in a similar direction as the LiDCO system. The PCO system provided better agreement with LiDCO measurements over time when hemodynamic conditions were similar to those during initial calibration. Recalibration of the PCO system is recommended when hemodynamic conditions or pressure waveforms are altered appreciably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…One factor responsible for the apparent overestimation and variability of PulseCO values may be the production of hypotension itself. The PulseCO transformation involves an inverse relationship between the determination of SV and arterial pressure difference (10,24). Significant decreases in blood pressure could result in an artificial increase in calculated SV, and thereby CO, unless a new calibration is performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor responsible for the apparent overestimation and variability of PulseCO values may be the production of hypotension itself. The PulseCO transformation involves an inverse relationship between the determination of SV and arterial pressure difference (10,24). Significant decreases in blood pressure could result in an artificial increase in calculated SV, and thereby CO, unless a new calibration is performed.…”
Section: Discussionmentioning
confidence: 99%
“…These patients, however, did not experience large changes in CO due to blood loss or periods of extreme hypotension. A recent experimental study in anesthetized dogs identified significant differences between CO derived by PulseCO vs. lithium dilution when deep planes of anesthesia were used to produce hypotension with a tendency toward overestimation of cardiac output (24). Another canine model found similar disparity between the two techniques when mild (10 mL/kg) to moderate (25 mL/kg) hemorrhage was performed (25).…”
mentioning
confidence: 96%
“…In some studies, haemodynamic instability secondary to vasodilatation causes pulse contour analysis to overestimate cardiac output [14,15], whereas in off-pump cardiac surgery, vasodilatation secondary to prostaglandin E 1 causes pulse contour analysis to underestimate cardiac output [16]. It was this latter pattern of change that we observed with epidural and general anaesthesia.…”
Section: Discussionmentioning
confidence: 57%
“…Despite this observation, the LOA and percentage error between the recalibrated and nonrecalibrated monitors increased substantially. Bias and LOA between CO monitors have typically been evaluated in light of substantial hemodynamic changes . Our results show that even mild changes in hemodynamic function that may affect blood pressure, but that are not substantial enough to alter CO, could still perturb the performance of a CCO monitor based on the arterial waveform analysis and raises the question on whether recalibration of monitors based on similar principles might be required more frequently than is presently assumed.…”
Section: Discussionmentioning
confidence: 85%